Worenine Prevents Solar Ultraviolet–Induced Sunburn by Inhibiting JNK2 - Xiao, Juanjuan; Lu, Hui; Ma, Tengfei; Ni, Xiaofang; Chang, Teding; Liu, Man; Li, Nijie; Lu, Peijiang; Ke, Changshu; Tian, Qin; Zou, Ling; Wang, Fei; et al. (Frontiers in Pharmacology, 2022)
Excessive solar ultraviolet radiation often causes dermatitis, photoaging, and even skin cancer. In the process of SUV-induced sunburn, JNK is activated by phosphorylation, which in turn phosphorylates its downstream transcription factors, such as ATF2 and c-jun, enhancing their transcriptional activityand further regulating the expression of genes, such as IL-6, which ultimately leads to dermatitis. Therefore, inhibiting JNK may be a strategy to prevent dermatitis. In this study,we screened for Worenine as a potential drug for inhibiting sunburn. Subsequently, we determined that Worenine inhibited the JNK-ATF2/c-jun signaling pathway,the secretion of IL-6 and TNF-αex vivo and in vivo, confirming the role of Worenine in inhibiting sunburn.And, we confirmed that Worenine bound and inhibited JNK2 activity in vitro through MST assay, kinase array and in vitro kinase assay. Therefore, Worenine might bea promising drug for the prevention and treatment of SUV-induced sunburn.